TINDAK PIDANA PENCUCIAN UANG OLEH PELAKU KORPORASI DITINJAU DARI ASAS KEADILAN (PUTUSAN NOMOR 75/PID.SUSTPK/2022/PN JKT PST, PUTUSAN NOMOR 24/PID.SUS-TPK/2023/PN JKT.PST DAN PUTUSAN NOMOR 12/PID.SUS-TPK/2023/PN SRG) - Silean, Yosua; Wahid, Eriyantouw; Multiwijaya, Vientje Ratna (Ensiklopedia of Journal, 2025)
The crime of money laundering is a process or act that aims to hide or disguise the origin of money or assets, obtained from the proceeds of a crime which are then converted into assets that appear to come from legitimate activities. This means that the money that is hidden is actually obtained illegally by carrying out actions that are also against the law, but is attempted in such a way that the source of the money appears to come from legitimate actions and is justified by law. Decision Number 12/Pid.SusTPK/2023/PN Srg DENI EDI RISYADI as a Civil Servant or State Administrator as a NonPermanent Employee at the Lebak Regency Land Office based on the Decree of the Head of the Lebak Regency Land Office committed a crime of corruption carried out jointly and a crime of money laundering. The responsibility of the perpetrator of the crime of money laundering originating from the proceeds of the crime of CORRUPTION as referred to in Article 1 number (9) of Law No. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering is every person and corporation. The basis for the judge's considerations in sentencing the perpetrator of the crime of money laundering is by considering the legal facts revealed in the trial and must have strong considerations in handing down a sentence that can have a deterrent effect on the defendant. Keywords: Criminal Acts, Money Laundering, Corporations, Corporate Actors.